Design and synthesis of novel androgen receptor antagonists via molecular modeling. Issue 4 (15th February 2016) - Zhao, Chao; Choi, You Hee; Khadka, Daulat Bikram; Jin, Yifeng; Lee, Kwang-Youl; Cho, Won-Jea
Graphical abstract: Abstract: Several androgen receptor (AR) antagonists are clinically prescribed to treat prostate cancer. Unfortunately, many patients become resistant to the existing AR antagonists. To overcome this, a novel AR antagonist candidate called DIMN was discovered by our research group in 2013. In order to develop compounds with improved potency, we designed novel DIMN derivatives based on a docking study and substituted carbons with heteroatom moieties. Encouraging in vitro results for compounds1b, 1c, 1e, 3c, and4c proved that the new design was successful. Among the newly synthesized compounds, 1e exhibited the strongest inhibitory effect on LNCaP cell growth (IC50  = 0.35 μM) and also acted as a competitive AR antagonist with selectivity over the estrogen receptor (ER) and the glucocorticoid receptor (GR). A docking study of compound1e fully supported these biological results. Compound1e is considered to be a novel, potent and AR-specific antagonist for treating prostate cancer. Thus, our study successfully applied molecular modeling and bioisosteric replacement for hit optimization. The methods here provide a guide for future development of drug candidates through structure-based drug discovery and chemical modifications.